Research on the impact path of China’s environmental protection investment on green development—based on the perspective of industrial structure upgrading - Guo, Mengyao; Cui, Yiniu (Frontiers in Environmental Science, 2024)
As a special category of investment, environmental protection investment can provide important funds and technological support for a region, achieve green production, and promote green development. This article uses a benchmark regression model based on panel data from 30 provinces in China from 2007 to 2020 to analyze the impact of environmental protection investment on the level of green development. It specifically examines the effects of urban environmental infrastructure investment, industrial pollution control investment, and completion of environmental protection acceptance projects on the level of green development. It also explores how different regions can make use of environmental protection investment according to local conditions. Additionally, due to the spatial spillover effect of environmental protection investment, this article introduces the spatial Durbin model to study the spillover effects. Furthermore, in order to effectively promote green economic development through environmental protection investment, it is necessary to upgrade the industrial structure. Therefore, this article also uses the mediation effect model to explore the relationship between environmental protection investment, industrial structure upgrading, and the level of green development. The research findings are as follows: (1) environmental protection investment can promote the development of green level; (2) the various components of environmental protection investment have different effects on the level of green development. Urban environmental infrastructure investment has a promoting effect on the level of green economic development, while industrial pollution control investment and completion of environmental protection acceptance projects have a restraining effect; (3) environmental protection investment has a positive spillover effect in spatial terms, promoting the green development of surrounding areas while driving the local green development level; (4) as an important driving force for promoting green economic development, environmental protection investment relies on the support of industrial structure upgrading, and further optimization and upgrading of the industrial structure can achieve green economic development. Based on these findings, this article proposes that each region should increase environmental protection investment, implement the concept of green development, and leverage the positive impact of each component of environmental protection investment on local green development according to local conditions.